Bibliometric Analysis of Corporate Innovation Strategy - Loso Judijanto (Westscience Press, 2026)
This study aims to map the intellectual structure, research trends, and emerging themes in the field of corporate innovation strategy using a bibliometric approach. Data were collected from a reputable academic database and analyzed using bibliometric techniques, including co-occurrence and network visualization with VOSviewer. The findings reveal that innovation and corporate strategy constitute the core of the research domain, indicating that innovation is widely positioned as a central mechanism in shaping firm performance and competitive advantage. The analysis also identifies several major thematic clusters, including strategic management and competitiveness, sustainability and corporate social responsibility, and knowledge and research development. Furthermore, the overlay and density visualizations highlight a noticeable shift in recent studies toward sustainability-oriented innovation, digital transformation, and responsible business practices. These results suggest that the field is evolving from a firm-centric and competition-driven perspective toward a more integrated framework that incorporates environmental, social, and technological dimensions. This study contributes to the literature by providing a comprehensive overview of the development of corporate innovation strategy and by identifying potential directions for future research, particularly in the areas of sustainable and digitally enabled innovation.